Improved Time Domain Substructural Damage Identification Method on Large-Span Spatial Structure. (23rd October 2021) - Yang, Taoyuan; Liu, Kun; Nie, Guibo
Abstract : The large-span spatial structure is a complex structural type with large number of elements, which makes health monitoring difficult. A time domain global substructural identification method was proposed in this paper to identify the local damage for the large-span spatial structure. The proposed method was an improvement method based on the time domain substructural identification method, which can identify the damage with a reduced structural model, and explicit force identification method, which can give convergent force identification result with incomplete response measurements, and it can assess one or more target substructures without knowing the conditions of the other parts of the structure. The application of the new method to large-span spatial structure was presented, and then an improved global method was proposed to further reduce the computation time and promote it in practice. Two orthogonal spatial square pyramid grid structure models are constructed to validate the time domain global substructural method and the improved global method. The results show that the time domain global substructural damage identification method identifies the small local damage in multiple members with satisfactory accuracy and the improved global method effectively shortens identification time.